REDUCING ANXIETY IN MIDDLE-AGED HYPERTENSIVE PATIENTS THROUGH DHIKR RELAXATION - Fitri, Khairunnisa; Nashori, Fuad (Psikoislamedia: Jurnal Psikologi, 2024)
Hypertension is a life-threatening disease often referred to as a silent killer. Dhikr relaxation is one method aimed at providing both physical and psychological tranquility to hypertensive patients. Among the psychological symptoms experienced by hypertensive patients is anxiety. This motivated the researchers to provide an intervention in the form of dhikr relaxation to alleviate the anxiety in middle-aged hypertensive patients. A total of 20 hypertensive patients participated in this study, divided into two groups: an experimental group consisting of 10 individuals and a control group consisting of 10 individuals. It also applied a pretest-posttest control group design, with measurements taken three times (pretest, posttest, and follow-up). The anxiety measurement tool used in this study was the GAD-7 (Generalized Anxiety Disorder-7) developed by Spitzer et al. Then the researchers conducted Mann-Whitney analysis. The results of the study indicated that dhikr relaxation is effective in reducing anxiety in the middle-aged hypertensive patients.